PRODUKSI BAKTERIOSIN OLEH Lactobacillus plantarum DJ3 DAN APLIKASINYA SEBAGAI PENGAWET DAGING - Hariani, Liliek (El-Hayah : Jurnal Biologi, 2013)
Lactic acid bacteria (LAB) are able to inhibit other bacteria by producing protein, named as bacteriocin. Bacteriocin whichÂ  produced by LAB is useful to inhibit pathogenic bacteria that harmful to human health or even makes food spoil. Bacteriocin is effective as antibacterial agent against pathogenic bacteria. Crude Extract of bacteriocin that produced by Lactobacillus plantarum DJ3 is able to inhibits the growth of E. Coli (4 mm) and S. aureus (5.33 mm). Application of bacteriocin in beef show that it able to inhibita the growth of bacteria. The amount of bacteria in beef that stored in 8 hours with bacteriocin addition are 1,3 X 108 CFU/g, and 3.7 XÂ  108 CFU/g without bacteriocin addition. While the amount of bacteria in beef that stored in 12 hours with bacteriocin addition are 2.0 x 109 CFU/g and 1.5 x 1011 without bacteriocin addition